The importance of context: re-examining the ‘deployments’ of SWAT teams in Canada - Lair, Zachary (Policing and society, 2024)
Based on an analysis of data released through Freedom of Information (FOI) requests, Canadian researchers have suggested that Special Weapons and Tactics (SWAT) teams are no longer exclusively deployed to resolve high-risk incidents but now frequently respond to routine calls that do not necessitate their involvement. Given concerns about these conclusions, we submitted the same FOI requests to the 14 police agencies examined by Roziere and Walby [2020. Special weapons and tactics teams in Canadian policing: legal, institutional, and economic dimensions. Policing and society, 30 (6), 704–719] and worked with the FOI analyst from each agency to ensure that the data were being interpreted correctly. Based on our re-analysis of the FOI-released data, we report on two problems with the conclusions reached by Roziere and Walby: the conflation of incidents where any SWAT officer responds to calls with full SWAT team deployments and the masking of potential risk factors in calls when relying on call type categories. Our findings illustrate the value of police agencies disclosing relevant contextual information to researchers when possible and they reinforce the necessity of collaborating with FOI analysts to better understand the data being released.